Addition of Neuromuscular Taping in Kegel Exercise For Increasing Pelvic Floor Muscles of the Urine Incontinence in Middle-aged Individuals - ., Ismaningsih; Muawanah, Siti (KnE Life Sciences, 2021)
Urine incontinence is the loss of bladder control, or leaking urine. The current study aimed at providing a physiotherapy intervention such as adding neuromuscular taping to Kegel exercises for increasing the pelvic floor muscles. The study was conducted at the Wredha Khusnul Khotimah house in Pekanbaru. The study is an experimental research with a randomized pre- and post-test group design, and made a comparison between the two groups. The study compared the RUIS (Revised Urinary Incontinence Scale) scale value before and after the intervention. The study sample comprised of 20 middle-aged people with urine incontinence condition who were recommended neuromuscular taping in addition to their Kegel exercises for six weeks. Mann Whitney test found p-value < 0.05, so it could be concluded that there was a difference between the RUIS value before and after the intervention in both groups. The addition of neuromuscular taping to Kegel exercises is more effective than Kegel exercise alone for urine incontinence condition in middle-aged individuals. Keywords: neuromuscular taping, elderly, urine incontinence